Farmer Community-Based River Ecotourism Model in Gowa Regency - Taba, Muhammad Idrus; Parawansa, Dian AS; Ismail, Muhammad (E-Journal of Tourism; Volume 10 Number 1 (March 2023), 2023)
Tourism is one of the leading business sectors that continues to develop in academic studies. This study aims to reveal a model of tourism activity development in supporting community business improvement in the Biroro Bontolerung River Area, Gowa Regency. The method applied is descriptive-qualitative with unit analysis of product resources and social resources at the research site. This research has identified the concept of tourism activities that are suitable to be developed in the Biroro Bontolerung River Area based on the concept of experiential tourism. Furthermore, this research has resulted in mapping the interests and interests of relevant stakeholders, to be studied further in making development decisions for the government and the community.